2020
DOI: 10.1097/jcma.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between platelet/lymphocyte ratio and prognosis of patients with septic acute kidney injury: A pilot study

Abstract: Background: To explore the potential role of the platelet/lymphocyte ratio (PLR) as a prognostic marker in septic patients with acute kidney injury (AKI) and to provide theoretical evidence for the epidemiological study of the prognosis of patients with septic AKI in its early stage. Methods: A pilot study was conducted. A logistic regression analysis was conducted to screen the risk factors, and the selected factors were performed using multiple logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Furthermore, another study indicated that an NLPR of ≥15.48 was associated with 28-day mortality in septic patients, which is concordant with the association of higher NLPR values with AKI and mortality in the present study [42]. In line with the current findings, several studies found an association between high PLR levels, high SII-index values and mortality [33,34,43,44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, another study indicated that an NLPR of ≥15.48 was associated with 28-day mortality in septic patients, which is concordant with the association of higher NLPR values with AKI and mortality in the present study [42]. In line with the current findings, several studies found an association between high PLR levels, high SII-index values and mortality [33,34,43,44].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there was no association between the modified DNI, MLR, PLR and SII index and the occurrence of AKI. Although there are some previous studies that suggested that these ratios are associated with AKI, they were performed in other settings (e.g., postoperative or ICU) or with other types of ratio measurements (e.g., DNI requires measuring myeloperoxidase-reactive cells and a nuclear lobularity assay) [28,[31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…1.003-1.039). 61 Another recent systematic review 62 also echoed that an elevated PLR is associated with severe illness in COVID-19 patients than in those with mild disease (SMD: 0.68; 95% CI: 0.43-0.93; I 2 = 58%).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to be elevated in response to many acute as well as chronic proinflammatory conditions 54–56 and associated with a poor prognosis in patients with COPD 57 and carcinomas 58–60 . A recent study has found a correlation between raised PLR and poor prognosis of sepsis‐induced acute kidney injury, and mortality (OR: 1.02, 95% CI: 1.003–1.039) 61 …”
Section: Discussionmentioning
confidence: 99%
“…Studies were conducted in China ( n = 4) [ 12 , 22 – 24 ], Indonesia ( n = 3) [ 16 , 19 , 20 ], Turkey ( n = 3) [ 10 , 11 , 18 ], Iran ( n = 1) [ 14 ], Serbia ( n = 1) [ 13 ], Saudi Arabia ( n = 1) [ 9 ], Poland ( n = 1) [ 17 ], Korea ( n = 1) [ 15 ], and India ( n = 1) [ 21 ]. Seven studies reported one-month mortality [ 9 , 10 , 12 , 15 , 19 , 21 , 24 ], three studies reported in-hospital mortality [ 13 , 14 , 22 ], and one study investigated ICU mortality [ 17 ]. Five studies did not report any data in this regard [ 11 , 16 , 18 , 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%